Compassion for all: Real-world online donations contradict compassion fade - Dominik S. Meier (University of Basel, Center for Philanthropy Studies (CEPS), 2023)
Research has shown that people are more likely to donate money to help a single victim rather than a group of victims. However, recent studies have been able to reverse this compassion fade effect by presenting people with multiple donation appeals with different victim group sizes (joint evaluation) instead of just one donation appeal (separate evaluation). The reversal of this effect when people evaluate multiple donation requests at once has important implications for fundraising. This study tests whether this effect can be replicated in the field by using data from GoFundMe, the world's largest crowdfunding platform. When browsing projects on GoFundMe, people see multiple projects displayed at once, placing them in a joint evaluation context. Using the project campaign category and description to control for confounding, I find that there is indeed a positive effect of the perceived victim group size on the amount of funds raised by a project.
Keywords: 330; Crowdfunding; compassion fade; fundraising; donations; identifiable victim effect